شیخ محمود سعید ممدوح: شخصیت اورعلمی خدماتSheikh Maḥmūd Saīd Mamdūḥ: Personality and Scholarly Contributions (Al-Qamar, 2021)
Sheikh Maḥmūd Saīd Mamdūḥ was expert in many departments of religious and Islamic studies. Although he got his master’s degree in agriculture as well as get Islamic education by many scholars of Arab. He wrote many books. Introduction of few books is as under. His famous book al-Tarīf in which he tried to explain the authenticity of Ḥadīths. In this book 846 Hadiths declared Ṣaḥīḥ by him. His book Bashārāt al Mūmin is to explain accuracy of a Ḥadith اتقوا فراسۃالمومن فانہ ینظر بنور اللہ. Tay al-Qirtas is about Ahl-e-Baīt. He collected Hadiths about family of Prophet (ﷺ). Tojīḥ al Aaīma is his criticism to a collection of Fatāwā. Which were published from Saʾudī Arabīa. A book al-Taqīb Al Amjad is explanation of   من لغافلا جمعۃلہ. Tazīn Al Alfāẓ is biography of Ḥufāẓ-e-Ḥadīth. There are 19 biographies in this book. Al Qawl Al Mastaofī is about explanation of Ḥadith من خرج من بیتہ الی الصلاۃ. Al Itijāḥāt al-Ḥadīthīa is biography of scholars of fourteenth century AH. Al-Ālām is criticism of a Fatwā of Ibn-e-Taimyyah.
Keywords: Shaikh Mamdūḥ; Muslim scholar; Ḥadith